Towards a prospective vision about master of computer science of Centroccidental Lisandro Alvarado University (Publicaciones en Ciencias y Tecnología, 2015)
This review highlights some important statistical data for a brief historical review of the Master of Computer Science of the Faculty of Science and Technology at Universidad Centroccidental “Lisandro Alvarado” in their different specialties: Artificial Intelligence, Computer Networks and Software engineering, and further, exposing what academic prospects are proposed to overcome the current demands that this master program faces.
Keywords: Computer Science; academic perspectives; artificial intelligence; computer networks; software engineering